Penerapan Model Project Based Learning (PJBL) Untuk Meningkatkan Kemampuan Menulis Teks Rekon Pada Siswa Kelas X SMK Negeri 1 Sukawati 2022/2023 - Elfrida Ayu Ahsari (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
Action research in the classroom (PTK) is being conducted in this study with the goal of helping students become more proficient writers of recon texts and replies to learning activities for the classroom. However, the study has not yet met the success requirements. The class average reaching a minimal level of 80 as the limit value for the minimum completeness criteria (KKM) with completion being primarily 75%, is one of the success markers that have not been met. Using the Project Based Learning (PJBL) approach helps improve students' motivation and text-writing skills. Recon for SMK Negeri 1 Sukawati's class X TKJ pupils for the 2022–2023 school year. 2. Using the Project Based Learning (PJBL) approach can boost the positive feedback that students in class X TKJ provide.